Aquilaria crassna leaf extract selectively upregulated calreticulin surface expression, a pro-phagocytotic signal, in triple-negative breast cancer cells - Pho-on, Pinyada; Sudsaward, Sangkab; Wongwad, Eakkaluk; Ingkaninan, Kornkanok; Khunchai, Sasiprapa (Asian Health, Science and Technology Reports, 2023)
During the last decade, studies of anti-cancer properties of extracts from several parts of Aquilaria species including Aquilaria crassna (A. crassna) Pierre ex Lecomte have been more attractive. Leaf extract of A. crassna Pierre ex Lecomte (AE) has been reported for medicinal activities except for anti-cancer activity in particular the enhancement of cancer-immune responses. Strategies that alter cancer phenotypes to be more sensitive to immune cell killing and/or to activate immune responses have become promising approaches for cancer therapy. We are interested in a strategy that sensitizes surviving cancer cells to express surface molecules for the enhancement of cancer cell killing by immune cells called immunogenic modulation. Thereby, this study aims to investigate the induction effect of AE on the expression of molecules reported for immunogenic modulation which are the surface expressions of calreticulin (ectoCRT), a major histocompatibility complex class I (MHC class I), and CD95/Fas death receptor. M.D. Anderson-Metastatic Breast 231 (MDA-MB 231) cell line, a triple-negative breast cancer; TNBC, was treated with various concentrations (0- 640 µg/ml) of AE for 6 hr and 12 hr and examined for the cytotoxic effect by MTT assay. The results showed that concentrations of 20-640 µg/ml of AE treatment significantly decreased the percentages of cell viability at both time points. Sublethal doses (20-320 µg/ml) caused the cell viability > 70% were further examined for the surface expressions of ectoCRT, MHC class I, and CD95 using surface immunostaining and analyzed by flow cytometer. At 12 hr after treatment, AE selectively induced ectoCRT expression but did not show any effect on MHC class I and CD95 expressions in all AE-treated populations. To further clarify the involvement of AE-induced ectoCRT in an immunogenic modulation, AE-treated living cells were chosen to investigate the expression of ectoCRT. Our results found that AE-treated living cells showed a significant increase in the relative mean fluorescence intensity (relative MFI) of ectoCRT expression and a trend to increase in ectoCRT-positive cells compared to the untreated group (0 µg/ml). Together, this is the preliminary result reporting the upregulation of ectoCRT expression by AE. In addition, AE-induced ectoCRT has been mainly found in surviving/living cells which is accorded to the criteria of immunogenic modulation. However, the role of AE-induced ectoCRT in the enhancement of cancer cell killing especially in immune cell phagocytosis needs to be further investigated.